2020
DOI: 10.3390/f11050602
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topography on Long-Term Spontaneous Development of Soil and Woody Cover on Graded and Untreated Overburden

Abstract: We studied the development of soil and soil fauna, as well as selected vegetation parameters important for litter input into soil, in two chronosequences of postmining sites after opencast lignite mining near the town of Most (Czechia). Both chronosequences did not have tree planting. On the first chronosequence, no leveling or any other measures had taken place after heaping, and the site kept the wavelike appearance created by the dumping process. The second chronosequence was formed by sites levelled by ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is likely caused by craters becoming the focal points for runoff, litter and sediment deposits (Hupy & Schaetzl, 2006, 2008; Seibert et al, 2007). Other factors that could have affected the organic matter content include the position, slope or elevation of the craters (Guo et al, 2013), soil moisture and surface runoff into craters (Seibert et al, 2007; Zhang et al, 2012), plant growth favouring depressions rather than flat areas (Hupy & Schaetzl, 2008; Vicentini et al, 2020), earthworm activity (Hupy & Schaetzl, 2008), soil type and underlying geology (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely caused by craters becoming the focal points for runoff, litter and sediment deposits (Hupy & Schaetzl, 2006, 2008; Seibert et al, 2007). Other factors that could have affected the organic matter content include the position, slope or elevation of the craters (Guo et al, 2013), soil moisture and surface runoff into craters (Seibert et al, 2007; Zhang et al, 2012), plant growth favouring depressions rather than flat areas (Hupy & Schaetzl, 2008; Vicentini et al, 2020), earthworm activity (Hupy & Schaetzl, 2008), soil type and underlying geology (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bartuska & Frouz (2015) concluded that litter input increased at young sites and peaked after canopy closure at older sites but then stabilised or decreased. Vicentini et al 2020 showed that annual litter production was 182.1 g m À2 of the herb litter and 156.4 g m À2 of woody litter in 30 years old spontaneous sites in lignite mine. However, woody and herb cover can vary even after 30 years between 0 and 90%.…”
Section: Sequestration Ratementioning
confidence: 98%
“…Author details 1 Saint-Petersburg State University, Saint-Petersburg, Russia. 2 All-Russia Research Institute for Agricultural Microbiology, Saint-Petersburg, Russia. • support for research data, including large and complex data types • gold Open Access which fosters wider collaboration and increased citations maximum visibility for your research: over 100M website views per year…”
Section: Abbreviationsmentioning
confidence: 99%
“…Terrestrial ecosystems of industrial and urbanized territories are very different from natural landscapes. The urbanization process leads to a radical disruption of natural ecosystems, while the industrial development of resources, including mining, often ends with the complete destruction of the soil and vegetation cover [ 1 , 2 ]. Partial transformation or significant disturbance of ecosystems is an urgent problem of modern ecology and nature management, which must be solved also by introducing of ecological management elements.…”
Section: Introductionmentioning
confidence: 99%